Effication of Viral Nervous Necrosis DNA as Vaccines for Cromileptes altivelis - Wiwien Mukti Andriyani; Sri Murtini; Alimuddin Alimuddin (Universitas Muhammadiyah Malang, 2020)
Viral nervous necrosis (VNN) is a disease that often infects groupers. It has caused mass death in more than 34 species of marine fish. DNA vaccination might become a solution againts the infection. The construction of the pmBA-CP DNA vaccine consisting of the beta-actin promoter of medaka fish (Oryzias latipes) and capsid protein (CP) encoding VNN RNA2 has been made in previous studies. This study aimed to test the efficacy of the pmBA-CP DNA vaccine for VNN. The experiment consisted of two stages, namely (1) detection of anti-VNN antibody induction in vaccinated fish using ELISA, and (2) challenge test for fish vaccinated with the VNN virus. Grouper (body length 8 cm to 10 cm) were divided into two groups with a density of 5 fish 60 L–1. The fish in the first group were vaccinated with pmBA-CP intramuscularly at a dose of 12.5 µg per fish, while the second group of fish were not vaccinated. Antibody titer testing was carried out before treatment, and 1 d, 7 d, 14 d, 21 d, 28 d, and 35 d after vaccination. The challenge test was carried out on the 60th day after vaccination. The results showed that the S / P ratio in the vaccinated fish serum was higher than unvaccinated fish at 21 d to 35 d post-vaccination. DNA vaccination was able to induce anti-VNN antibodies of grouper. The results of the challenge test for vaccinated fish using VNN virus titer 103.5 FID50/0.2 mL showed 60% of survival rate. Thus, the pmBA-CP DNA vaccine could be useful for increasing grouper immunity, and support production of grouper.